Dinamika Fragmentasi Khalayak dalam Konsumsi Konten Budaya Lokal: Analisis Konten TikTok @mas_ijals - Abdul Rohim (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to analyze the dynamics of audience fragmentation in the consumption of local cultural content on the TikTok platform, particularly through the @mas_ijals account, which actively promotes Javanese culture. The phenomenon of audience fragmentation, triggered by advances in digital technology, has shifted media consumption patterns from mass to more segmented due to algorithms and individual preferences. Amidst the current of globalization that threatens the preservation of local culture, understanding cultural content consumption patterns in digital media is crucial for developing effective cultural preservation strategies. This study uses a qualitative approach with a constructivist paradigm to understand the meanings constructed by creators and audiences through interactions with local cultural content. Data were collected through in-depth interviews with one content creator and twelve active audiences, as well as an analysis of five videos with high engagement levels from the @mas_ijals TikTok account. Data validity was maintained through source triangulation and member checking to ensure the accuracy of interpretation. The results of the study reveal three main themes: first, local aesthetics have a strong personal appeal, with content packaged visually and narratively able to build emotional bonds and cultural understanding in the audience; Second, the TikTok algorithm acts as a cultural curator that regulates content distribution, although this distribution does not always align with the creator's target audience, thus giving rise to the challenge of fragmentation; and third, the formation of digital communities as spaces of cultural identity, where audiences collectively construct and reconstruct cultural meaning through active interaction. This research shows that despite the challenges of fragmentation and algorithmic constraints, the TikTok platform has great potential to become an effective medium for the preservation and dissemination of local culture if creators are able to understand and adapt to distribution mechanisms and audience preferences.